Simple Green Routes for Metal-Bixin Complexes Synthesis Using Glycerol-Based Deep Eutectic Solvent - Winda Rahmalia; Anis Shofiyani; Yohana Sutiknyawati; Septiani Septiani (Indonesian Journal of Chemistry, 2022)
Bixin is a natural dye belonging to the carotenoid group that has been reported to have many health benefits. In this work, for the first time, metal-bixin complexes were synthesized through a simple green route using deep eutectic solvent (DES) as reaction media. DES was produced by stirring choline chloride and glycerol with a molar ratio of 1:3. The metal-bixin complex was prepared by grinding and stirring bixin and divalent metal ions (Mg2+, Ca2+, Zn2+, Cu2+, separately) in DES at room temperature. DES formed in this work was a homogeneous colorless liquid with a freezing point below -20 °C. It has a pH, density, viscosity, and conductivity of 7.13, 148.99 cP, 1.207 g/cm3, and 1.8 mS/cm, respectively. UV-Vis spectrophotometric analysis shows that the absorption spectra produced by the Mg(II)-bixin, Ca(II)-bixin, Zn(II)-bixin, and Cu(II)-bixin complexes show an insignificant shift in the direction of a larger wavelength (red shift) compared to pure bixin. Spectral fine structure expressed as %III/II, i.e., the ratio of the height of the longest-wavelength absorption to the middle absorption peak. The value of %III/II for bixin, Mg(II)-bixin, Ca(II)-bixin, Zn(II)-bixin, and Cu(II)-bixin are 16.77, 20.37, 17.39, and 13.52%, respectively. The results of the FTIR spectra analysis confirmed that the bond between bixin and metal ions occurred in the carboxylate acid group, indicated by a decrease in the absorption intensity at wavenumber 3389 and 1716 cm−1.